2008
DOI: 10.1590/s1516-89132008000600010
|View full text |Cite
|
Sign up to set email alerts
|

Ketoconazole- and fluconazole-induced embryotoxicity and skeletal anomalies in wistar rats: a comparative study

Abstract: Ketoconazole and fluconazole are two broad-spectrum azole antifungals used for the treatment of superficial and systemic mycoses. Embryotoxicity and teratogenicity have been reported in some studies when those drugs are administered at high doses to pregnant rats. The aim of this study was to present a comparative study of embryotoxic effects as well as the skeletal anomalies in fetuses of Wistar rats which received ketoconazole and fluconazole at teratogenic doses on gestational days (GD) 6 through 15 (organo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…Imbalance in RA metabolism caused by triazoles has been demonstrated both in vitro and in vivo (Marotta and tiboni, 2010). An increased level of endogenous RA was the suggested mechanism behind altered craniofacial morphogenesis such as cleft palate and reduced ossification of skull bones after in utero exposure to ketoconazole (Amaral and Nunes, 2008). Another possible mechanism for the developmental toxicity of conazole compounds might be via blocking of cardiac potassium channels.…”
Section: Introductionmentioning
confidence: 99%
“…Imbalance in RA metabolism caused by triazoles has been demonstrated both in vitro and in vivo (Marotta and tiboni, 2010). An increased level of endogenous RA was the suggested mechanism behind altered craniofacial morphogenesis such as cleft palate and reduced ossification of skull bones after in utero exposure to ketoconazole (Amaral and Nunes, 2008). Another possible mechanism for the developmental toxicity of conazole compounds might be via blocking of cardiac potassium channels.…”
Section: Introductionmentioning
confidence: 99%
“…These drugs are metabolised primarily in the liver, therefore control of liver enzymes is recommended. They have teratogenic activity (class C) and should not be used during pregnancy (4,53) . The imidazoles used more often in ophthalmology include miconazole (MCZ), econazole (ECZ) and ketoconazole (KCZ).…”
Section: Azolesmentioning
confidence: 99%
“…Similar to KCZ, gastric absorption depends on a low pH. Studies in rats showed that ICZ has a lower teratogenic risk than KCZ (53) . Systemic administration at 400 mg/day was effective in the treatment of infections by Candida spp.…”
Section: -Itraconazolementioning
confidence: 99%
“…No Brasil, estes estudos são regulamentados pela Agencia Nacional de Vigilância Sanitária (ANVISA), Portaria № 116/MS/SNVS, de 8 de agosto de 1996 (Brasil, 1996). A regulamentação despertou interesse em pesquisa neste assunto, e gerou vários trabalhos científicos (Moller et al, 2003;Borges et al, 2005;Brandini et al, 2005;Amaral & Nunes 2008;Camargo et al, 2009).…”
Section: Introductionunclassified